The impact of the 2007-08 food price crisis in a major commodity exporter: Food prices, inflation, and inclusion in Brazil - Bernardo Mueller; Charles Mueller (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper argues that the effects of the food price crisis of 2007-08 put pressure on two variables that are of central importance to the Brazilian government: inflation and social inclusion. We describe how political institutions in Brazil in the past 25 years have given rise to a policy-making process where fiscal stability and social inclusion are the overarching priorities, irrespective of the party in power. In this scenario one would have expected that the food price crisis would have led to significant reactions by the government to safeguard those two central policy objectives. However, the reaction of the government and social groups was relatively subdued, compared to that in most other countries. We explain this apparent puzzle by showing that the negative impacts of the food price increases on consumers was partly counterbalanced by the benefits from agricultural production, given that Brazil is a major exporter of commodities. Also, before the crisis the country already possessed a series of programmes and mechanisms that offered social protection to the poor that could be easily and quickly adjusted. Brazil was therefore well-placed to deal with the impacts of the crisis.
Keywords: Q17; Q18; O13; F10; 330; food price; price transmission; Brazil; social inclusion